A facile one-pot synthesis of 2, 3-diarylated benzo[b]furans via relay NHC and palladium catalysis. Issue 6 (12th January 2016) - Jia, Yanyan; Li, Tuanjie; Yu, Chenxia; Jiang, Bo; Yao, Changsheng
Abstract : An efficient one-pot synthesis of 2, 3-diarylated benzo[ b ]furans was realized through the relay catalysis of N-Heterocyclic Carbene (NHC) and palladium from substituted 2′-bromodiphenylbromomethanes and aryl aldehydes. Abstract : An efficient one-pot synthesis of 2, 3-diarylated benzo[ b ]furans was realized through the relay catalysis of N-Heterocyclic Carbene (NHC) and palladium from substituted 2′-bromodiphenylbromomethanes and aryl aldehydes. The easy availability of the starting materials, good compatibility of catalysts, convergent assembly and concomitant modification of the target scaffold, and potential utilization value of the products make this strategy attractive in organic synthesis.